Conjugated polymer P3HT–Au hybrid nanostructures for enhancing photocatalytic activity1. Issue 23 (21st June 2015) - Jana, Bikash; Bhattacharyya, Santanu; Patra, Amitava
<x xml:space="preserve">Abstract</x> Organic–inorganic hybrid nanostructures for designing new optical based materials for efficient photocatalysis.